Directly fabricated Al2O3/GdAlO3 eutectic ceramic with large smooth surface by selective laser melting: Rapid solidification behavior and thermal field simulation. Issue 3 (March 2022) - Shen, Zhonglin; Su, Haijun; Liu, Haifang; Zhao, Di; Liu, Yuan; Guo, Yinuo; Fan, Guangrao; Yu, Minghui; Chen, Jun; Guo, Min; Zhang, Jun; Liu, Lin; et al.
Abstract: Selective laser melting (SLM), a novel approach for one-step melting and solidifying ceramic powder beds layer by layer without post-process of degreasing and sintering, has been developed to directly prepare highly dense (>95 %) Al2 O3 /GdAlO3 (GAP) eutectic composite ceramics with large smooth surfaces. Compact net-shaped plates with the maximum size of 73 × 24 × 5 mm 3 are obtained by different strategies of laser pre-heating and multi-tracks' deposition without any binders. Combined with the finite element thermodynamic coupling simulation results, it is proved that the stress between the substrate and depositions during SLM can be greatly reduced by the step-up preheating, and thus effectively improving the ceramic forming quality. The macro-morphology, microstructure evolution, rapid solidification behavior and mechanical properties of the SLM-ed eutectic ceramics are systematically investigated at different laser processing parameters. The microstructure transforms from ultra-fine irregular eutectic to complex regular eutectic with the increase of the scanning rate. The average eutectic spacing, and solidification rate has an approximately linear relationship consistent with the Jackson-Hunt (JH) model. The microhardness and fracture toughness can reach 17.1 ± 0.2 GPa and 4.5 ± 0.1 MPa·m 1/2, respectively. The results indicate that SLM method is a highly effective technique for fabricating high-performance net-shaped structural composite ceramics.